Genotypic Variation and Resistance to Early Leaf Spot in Groundnut: Insights from Inoculated and Non-Inoculated Field Screening with Multivariate Analysis - Lawan, Zainab Miko; Usman, Alhassan; Mohammed, Mohammed Sagir; Umar, Muhammad Lawal; Ajeigbe, Hakeem Ayinde; Shittu, Emmanuel Abraham (Faculty of Natural and Applied Sciences Journal of Applied Biological Sciences, 2025)
Early leaf spot (ELS), caused by Cercospora arachidicola, is a highly damaging foliar disease that significantly restricts groundnut (Arachis hypogaea L.) production in West Africa, often causing yield losses of over 50% due to severe leaf defoliation and decreased pod and fodder output. Developing host plant resistance provides a sustainable and affordable approach to managing ELS, particularly benefiting smallholder farmers. This study aimed to assess the genetic variation in resistance to ELS among 183 groundnut minicore genotypes under both inoculated and non-inoculated field conditions during the 2019 rainy season at two known disease hotspots of Teaching and Research farm of Bayero University Kano and Samaru, ABU Zaria. The experiment was laid out in a 14 × 13 alpha lattice design with two replications. Data were collected on agronomic and disease-related traits including days to 50% flowering, pod weight, seed weight, kernel yield, fodder weight, disease incidence, disease scores at 65 and 90 days after sowing (DAS), disease severity, shelling percentage, harvest index, and number of hills at harvest. The data were analyzed using ANOVA, Principal Component Analysis (PCA), and cluster analysis. Highly significant genetic differences (p ≤ 0.05) were observed among the genotypes for both disease resistance and yield traits under both conditions, with no significant genotype × environment interaction. Genotypes such as SAMNUT 22, ICG 12991, ICG 3240, and ICG 4540 exhibited consistently low ELS incidence and high yield performance, identifying them as promising candidates for breeding programs. In contrast, SAMNUT 26, ICGV-IS 07213, and SAMNUT 24 showed high susceptibility to ELS. PCA revealed that the first two principal components accounted for over 75% of total variation, with pod and seed weights negatively associated with disease scores at 90 DAS. Cluster analysis grouped genotypes into four distinct clusters that did not align with eco-geographical origin, suggesting that genetic diversity is not strictly geography-dependent. These findings underscore the presence of exploitable genetic variability and the feasibility of incorporating ELS resistance into groundnut improvement pipelines. The identified resistant genotypes offer valuable genetic resources for developing high-yielding, disease-resistant groundnut cultivars suitable for West African production systems.